1991
DOI: 10.1016/0140-6736(91)90544-y
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, controlled trial of effectiveness of ampicillin in mild acute respiratory infections in Indonesian children

Abstract: The recommended treatment for mild acute respiratory infections (ARI) in children is supportive care only, but many physicians, especially in developing countries, continue to prescribe antibiotic treatment because they believe it prevents progression to more severe ARI. To find out whether ampicillin treatment conferred any benefit over supportive care alone, a randomised, controlled trial was carried out among 889 children (under 5 years) with mild ARI in Indonesia. 447 were randomly allocated ampicillin (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 9 publications
(2 reference statements)
0
6
0
1
Order By: Relevance
“…The results of a randomized controlled trial in West Java demonstrating that ampicillin plus supportive care offers no benefit over supportive care alone for treatment of mild respiratory tract infections in young Indonesian children, support this point. 22 Although bacterial pathogens can be found in up to 21% of acute diarrhea cases admitted to hospital, 7 most antibiotics consumed by our population were not likely to be effective. Resistance rates of enterotoxigenic Escherichia coli (ETEC) heat-labile toxin (LT) and heat-stable toxin (ST), the most frequent bacterial cause of acute diarrhea in children as well as adults in Indonesia, are 67% LT and 83% ST for ampicillin, 48% LT and 70% ST for trimethoprim-sulfamethoxazole, and 95% LT and 85% ST for tetracycline.…”
Section: Discussionmentioning
confidence: 78%
“…The results of a randomized controlled trial in West Java demonstrating that ampicillin plus supportive care offers no benefit over supportive care alone for treatment of mild respiratory tract infections in young Indonesian children, support this point. 22 Although bacterial pathogens can be found in up to 21% of acute diarrhea cases admitted to hospital, 7 most antibiotics consumed by our population were not likely to be effective. Resistance rates of enterotoxigenic Escherichia coli (ETEC) heat-labile toxin (LT) and heat-stable toxin (ST), the most frequent bacterial cause of acute diarrhea in children as well as adults in Indonesia, are 67% LT and 83% ST for ampicillin, 48% LT and 70% ST for trimethoprim-sulfamethoxazole, and 95% LT and 85% ST for tetracycline.…”
Section: Discussionmentioning
confidence: 78%
“…The Herne 1980 trial was translated from French to English. One paper was excluded because a placebo was not used in the control group (Sutrisna 1991).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Excluded as not randomised. Results: showed a benefit for chloramphenicol Sutrisna 1991 Excluded as there was no placebo control group. Results: antibiotic no better than control group Townsend 1960 Excluded as used prophylactic antibiotics.…”
Section: Sulman 1958mentioning
confidence: 99%
“…662 conclusions. Several studies have shown that it is possible to train CHWs to recognize and successfully treat pneumonia in newborn infants in community-based settings.…”
Section: Tba/chw Trainingmentioning
confidence: 99%